KEHIDUPAN LANJUT USIA ( LANSIA ) DI UPT PELAYANAN SOSIAL TRESNA WERDHA HUSNUL KHOTIMAH PEKANBARU - Sirait, Fitri Ningsih; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Aging process is a  natural process of living things Coslatte (Caseli and Lopez, 1996) said that aging is a biological process in human body continuosly in age level and time, while old age is the last process of that aging. In the social services in UPT Tresna Werdha Husnul Khotimah  Pekanbaru, there was many factors that causes the elderly lived in the social services. Among of them are because of the condition of the elderly had been displace in social and economical, they didn’t have any closer relatives or the member of the family that have their own work and careless. Social services UPT Tresna Werdha Husnul Khotimah Pekanbaru consist of 11 public servants (PNS), 36 honorary employee, is elderly officers, 6 nurses, 7 experts liker (Doctors, religion conselour, gymnastic instructor, trainer skill), 3 cooking services, 2 laudress, 5 stafs, 4 securities, 1 driver, and 1 administration. The strategy of  this research was purposive sampling. The method of this research was kualitatife descriptive and use the social theory of Max Weber that oriented the motiv and purpose of the accused. The result of this research shown that elderly decide to live and stay in UPT Tresna Werdha Husnul Khotimah Pekanbaru was caused of economical factor, distance factor, the bussines of their relatives and some of the elderly don’t want to bother their cildren and family to took care of them. Key Word : Life of elderly, social services